Zoledronic Acid for Periprosthetic Bone Mineral Density Changes in Patients With Osteoporosis After Hip Arthroplasty—An Updated Meta-Analysis of Six Randomized Controlled Trials - Liu, Yuan; Xu, Jia-Wen; Li, Ming-Yang; Wu, Li-Min; Zeng, Yi; Shen, Bin (Frontiers in Medicine, 2021)
Introduction: Periprosthetic bone mineral density loss following total hip arthroplasty may threaten the survival of the implant, especially in patients with osteoporosis. Zoledronic acid (ZA) is the representative of the third generation of bisphosphonates, which were effective in reducing bone loss in conditions associated with accelerated bone turnover. The aim of this study was to evaluate the efficacy and safety of ZA in patients with osteoporosis after THA. Methods: Randomized controlled trials (RCTs) associated with ZA and THA were searched from the MEDLINE, PubMed, EMBASE, Wanfang database, and the Web of Science (on Aug 2021). Other methods like hand search and email request were also tried. The methodological quality was assessed by the RoB 2.0. Relevant data were abstracted from the included RCTs, authors were contacted when necessary. Results: Six RCTs involving a total of 307 patients were finally included and analyzed. The pooled data demonstrated that significantly less periprosthetic BMD loss in Gruen zone 7 had occurred in the ZA-treated patients than in the control patients at three months (MD=4.03%; 95%CI: 0.29% to 7.76%; P=0.03), six months (MD=7.04%; 95%CI: 2.12% to 11.96%; P=0.005), and twelve months (MD=7.12%; 95%CI: 0.33% to 13.92%; P=0.04). The Harris Hip Score was also significantly increased in ZA group at 6 and 12 months after operation (P=0.03, P=0.02, respectively). Influenza-like symptom was found related to the usage of ZA (RR=7.03, P<0.0001). Conclusion: A meta-analysis of six randomized controlled trials suggested that zoledronic acid was beneficial in maintaining periprosthetic bone mineral density in patients with osteoporosis at 6, 12 months after THA. The Harris hip score was also significantly improved in patients treated with zoledronic acid. However, the short length of follow-up of the available studies resulted in the lack of analyses regarding the survival of implants including the rate of aseptic loosing, periprosthetic fracture and revision. It still needs to be determined in research with longer follow-up period.